Efektivitas Pengolahan Air Limbah Domestik Grey Water Dengan Proses Biofilter Anaerob dan Biofilter Aerob (Studi Kasus: IPAL INBIS Permata Bunda, Bontang) - Muhammad Busyairi; Nikita Adriyanti; Abdul Kahar; Dian Nurcahya; Sariyadi Sariyadi (Fakultas Teknik, 2020)
Domestic wastewater from non toilets is referred to as grey wastewater, domestic wastewater from bathing, washing and from the kitchen. Incubator Bisnis (INBIS) Permata Bunda is a forum for the application of entrepreneurial skills (apprenticeship) for people with disabilities residing in Kampung Aren, Bontang City, East Kalimantan. Grey wastewater treatment at INBIS Permata Bunda with a grease trap, filtration, sedimentation, anaerobic biofilter, aerobic biofilter, sedimentation and control. The research objective was to determine the effectiveness of INBIS Domestic WWTP to reduce organic pollutant loads based on the quality standard parameters of domestic wastewater from the Minister of Environment and Forestry Regulation No.P.68 of 2016 those are the parameters of pH, BOD, COD, TSS, fatty oil, ammonia, and total coliform. The domestic wastewater treatment process for grey wastewater has a reduced effectiveness ranging from 56.73% - 97.65% and has met the quality standards for the parameters, pH, BOD, COD, ammonia, fatty oil, and total coliform, but for TSS parameters and total coliform needs operational evaluation. Grey waterwater from the INBIS domestic wastewater treatment plant has the potential to become an alternative water source for watering plants (afforestation) if the processing results are in accordance with quality standards.